π–π interactions enable in-situ exfoliation of BN nanoflakes for high-performance thermal interface materials - Mingming Sheng; Junbin Lu; Hongyu Gong; Jincheng Yu; Jianqiang Bi; Weibin Zhang; Guowen Chen; Jianxin Li; Jie Jing; Yujun Zhang (Journal of Materiomics)
Boron nitride nanoflakes (BNNF) are rendered as ideal thermal conductivity fillers for thermal interface materials (TIMs) due to their ultrahigh thermal conductivity (TC) and superior electronic insulation. However, it is difficult to guarantee the high yield of well dispersed BNNF in the polymer matrix for industrial production. Herein, we propose a novel “in-situ exfoliation” strategy to fabricate the thin BNNF via chemical bonding engineering. By enhancing the π–π stacking between the inclusion and matrix, the average thickness of the BN is efficiently reduced during the three-roll mixing process. The as-prepared BNNF composite presents ultrahigh in-plane TC (10.58 W·m−1·K−1) with 49.5% (in mass) BN loading at 100 parts per hundreds of rubber (phr) with simultaneously enhanced flexibility. Notably, the tensile strength, the initial thermal decomposition temperatures (T5%) and elongation at break of the composite can reach 4.94 MPa, 470.6 °C and 98%, respectively. Our LED chip cooling tests validate the outstanding heat dissipation ability of the composites for TIM applications. Furthermore, this strategy also proves effective in exfoliating the graphite flakes, demonstrating excellent generalization capability. This work opens up a new avenue for developing the high-performance TIMs, showing huge potential in large-scale production.